Authentication of Geographic Origin of Wine by using EDXRF and Multivariate Statistics - Sudac; J. Obhođaš; A. Vinković; A. Kutle; V. Valković (Journal of Basic & Applied Sciences, 2019)
The controlled geographic origin of wine is value added and therefore of great interest to both consumers and manufacturers. It is widely accepted that soil is important component of a wine region terroir, but the reflection of the soil characteristics into the wine, and especially soil elemental composition which is very specific for each vineyard location, is not yet fully understood. By assuming that link between elemental composition of soil and wine exists, the discrimination technique Between Group - Principle Component Analysis (BG-PCA) was used on log(csoil)/log(cwine) ratios of elements Ca, Mn, Fe, Cu, Zn, Rb and Sr to find and evaluate differences between wine regions. The results have been shown for 16 wine samples of Graševina (variety of grapevine Riesling), which can be grouped in 5 viniculture regions of the continental part of the Republic of Croatia. Wine samples pre-concentrated by freeze drying and corresponding soil samples were analyzed by the EDXRF technique.